2020
DOI: 10.1038/s41568-020-0281-y
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil diversity and plasticity in tumour progression and therapy

Abstract: Neutrophils play a key role in defence against infection and in the activation and regulation of innate and adaptive immunity. In cancer, tumour-associated neutrophils (TANs) have emerged as an important component of the tumour microenvironment. Here they can exert dual functions. TANs can be part of tumour-promoting inflammation by driving angiogenesis, extracellular matrix remodelling, metastasis and immunosuppression. On the other hand, neutrophils can mediate antitumour responses by direct killing of tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
737
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 764 publications
(754 citation statements)
references
References 263 publications
(450 reference statements)
12
737
1
4
Order By: Relevance
“…In steady state, both circulating and tissue neutrophils are endowed with functional and phenotypic characteristics [ 16 , 116 ]. Accordingly, neutrophil heterogeneity has been associated with different parameters, such as maturation, ageing or activation states in response to signals from the tissue microenvironment, such as cytokines [ 19 ].…”
Section: Neutrophil Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…In steady state, both circulating and tissue neutrophils are endowed with functional and phenotypic characteristics [ 16 , 116 ]. Accordingly, neutrophil heterogeneity has been associated with different parameters, such as maturation, ageing or activation states in response to signals from the tissue microenvironment, such as cytokines [ 19 ].…”
Section: Neutrophil Heterogeneitymentioning
confidence: 99%
“…The role of neutrophils in tumour biology has long been underestimated while particular emphasis has been placed on the role of other myeloid cells, such as macrophages [ 12 , 13 ]. However, recent findings showed that neutrophils are an important component of the TME and have highlighted their importance in tumour progression as well as in the orchestration of pathways leading to tumour resistance [ [14] , [15] , [16] , [17] , [18] ]. These contrasting findings are likely the results of the previously underestimated plasticity and heterogeneity of neutrophils in cancer [ 8 , 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils are well known in infections of the organism. In tumors, tumor-associated neutrophils can induce angiogenesis, ECM remodeling, metastasis, and immunosuppression [37] . The function of these immune cells in the tumor microenvironment allows us to speculate whether the cells release special signals during the ferroptosis, so that mast cells and neutrophils promote angiogenesis and further promote the proliferation metastasis of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils represent another abundant component of innate immunity whose contribution in cancer has only started to be elucidated in the last few years ( 108 ). Neutrophils have been shown to boost lung metastasis from breast cancer ( 81 , 109 111 ) and to reawaken DDCCs ( 41 , 107 ).…”
Section: Mechanisms Of Survival Quiescence and Reawakening Of Ddccsmentioning
confidence: 99%